2016
DOI: 10.1080/09674845.2016.1144947
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology for lymph nodes: a three-year study

Abstract: Lymphadenopathy is associated with a wide range of disorders; however, metastatic lymph nodes of malignancies are the most common cause for enlarged lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…This high rate has been similarly reported by sev- eral studies in developing countries [1,3,4]. On the contrary, in developed countries, malignant tumors are the first cause of cervical lymphadenopathy [5].…”
Section: Discussionsupporting
confidence: 55%
“…This high rate has been similarly reported by sev- eral studies in developing countries [1,3,4]. On the contrary, in developed countries, malignant tumors are the first cause of cervical lymphadenopathy [5].…”
Section: Discussionsupporting
confidence: 55%
“…This may be due to higher prevalence of tuberculosis in our country . In other ethnic groups, metastatic tumors were found to be the most common cause of cervical lymphadenopathy in FNAC . Considering histology as the gold standard, FNAC has been found to have a very low FN rate, consisting in 0.2% of negative cases in our review.…”
Section: Discussionmentioning
confidence: 68%
“…In 2015, Wang et al [71] reported using this method to detect levels of the mRNA of a transcription factor (Snail) in pancreatic cancer. In issue 1 this year, Zhou et al [72] reported the result of FNAC examination of 2136 lymph nodes from 1362 patients with lymphadenopathy. The most common findings were metastatic tumours (present in 53.6% (far more prevalent in males [675 from 1178] than in females [470 from 958, chi-squared p < 0.001]), chronic non-specific lymphadenitis (15.2%) tuberculous lymphadenitis (8.7%) and reactive lymphadenitis (7.5%).…”
Section: Cytopathologymentioning
confidence: 99%